Student Worksheets Literacy-Based to Improve High-Level Thinking Skill - Sembiring, Irawati Br; Hadi, Wisman; Pramuniati, Isda (Randwick International of Education and Linguistics Science Journal, 2024)
This research is motivated by the lack of availability of LKPD that supports literacy activities to improve high-level thinking skills. This type of research is Research and Development (R&D) with the ADDIE model development method. The discussion of the research is adjusted to the ADDIE research and development procedures, namely: analyze, design, development, implementation, and evaluation. The subjects of this study were 24 students of grade V SDN 101867 Payagambar. Determination of the level of feasibility of LKPD or Student worksheets is based on expert validation tests and trials on students through student response questionnaires. The effectiveness of LKPD was obtained from the results of the pretest and posttest of grade V students. The results of this study indicate that the validation of material experts was 80% with a feasible category, validation of language experts was 85.41% with a very feasible category, validation of layout design experts was 90.47% with a very feasible category. The percentage results of the student response questionnaire were 86.70 which were categorized as very feasible, so it can be said that LKPD is feasible for use by grade V elementary school students. The results of the student pretest reached an average score of 69.3 with classical completeness reaching 42% with an incomplete category. While the results of the posttest after using LKPD reached an average of 84.50 with classical completeness reaching 100% and declared complete. Based on the pretest and posttest values, the gainscore value can be seen as 0.51 with a moderate effectiveness category. This shows that the use of literacy-based LKPD to improve high-level thinking skills has been effectively used by grade V students of SDN 101867 Payagambar, Batang Kuis District.